Newer Anticoagulants for Non-Valvular Atrial Fibrillation - Joseph M. Harburger; Wilbert S. Aronow (MDPI AG, 2012)
Non-valvular atrial fibrillation is a recognized risk factor for stroke and systemic embolism. It has been clearly established that warfarin reduces the risk of stroke and systemic embolism in persons with atrial fibrillation and additional risk factors for stroke. The use of warfarin, however, requires frequent monitoring, and there is great variability in patient response to warfarin. Warfarin interacts with several medications and foods. In addition, warfarin use portends a significant risk of bleeding. For these reasons, warfarin is frequently not prescribed to persons for whom the drug would provide a clear benefit. Over the past decade, attempts have been made to develop drugs that are at least as safe and effective as warfarin for the treatment of atrial fibrillation that do not require monitoring nor have as many interactions. Initial studies of compounds in this regard ultimately failed due to safety concerns, but over the past two years two novel agents have been approved by the United States Food and Drug Association for anticoagulation in non-valvular atrial fibrillation, another drug is under review, and additional compounds are being studied. This article will review the use of warfarin and these new agents in the treatment of non-valvular atrial fibrillation.